Palatal asymmetry assessed by intraoral scans: effects of sex, orthodontic treatment, and twinning. A retrospective cohort study - Botond Simon; Francesco Guido Mangano; Adrienn Pál; István Simon; Dalma Pellei; Arvin Shahbazi; János Vág (BMC, 2023)
Abstract Background Symmetry is critical in perceived attractiveness, especially in female faces. The palate determines the teeth' alignment and supports facial soft tissues. Therefore, the study aimed to assess the effects of sex, orthodontic treatment, age, and heritability on the directional, anti-, and fluctuational asymmetry in the digital palatal model. Methods The palate of 113 twins, 86 female and 27 male subjects, with and without previous orthodontic treatment, were scanned by the Emerald (Planmeca) intraoral scanner. Three lines were constructed horizontally in the digital model, one between the right and left first upper molars and two between the first molars and incisive papilla. Two observers calculated the left and right angles between the mid-sagittal plane and molar-papilla lines. The intraclass correlation coefficient was used to assess the inter-observer absolute agreement. The directional symmetry was determined by comparing the mean left and right angles. The antisymmetry was estimated from the distribution curve of the signed side difference. The fluctuating asymmetry was approximated from the magnitude of the absolute side difference. Finally, the genetic background was assessed by correlating the absolute side difference between monozygotic twin siblings. Results The right angle (31.1 degrees) was not significantly different from the left one (31.6 degrees). The signed side difference followed a normal distribution with a mean of -0.48 degrees. The absolute side difference (2.29 degrees, p < 0.001) was significantly different from zero and negatively correlated (r=-0.46, p < 0.05) between siblings. None of the asymmetries was affected by sex, orthodontic treatment or age. Conclusions The palate illustrates neither directional asymmetry nor antisymmetry, indicating that most people's palates are symmetric. However, the significant fluctuating asymmetry suggests that some subject has considerable asymmetry but is not influenced by sex, orthodontic treatment, age, and genetics. The proposed digital method is a reliable and non-invasive tool that could facilitate achieving a more symmetrical structure during orthodontic and aesthetic rehabilitation. Trial registration The Clinicatrial.gov registration number is NCT05349942 (27/04/2022).